The Role of Mosque Communities in Preventing Recidivism among Former Prisoners in Jakarta - Muhammad Naufal Afif (PERSPEKTIF, 2026)
Recidivism remains a significant challenge in the social reintegration of former prisoners, particularly due to persistent social and economic pressures after release. This study aims to analyze the role of mosque-based communities in providing religious guidance as a mechanism for preventing recidivism among former prisoners in Jakarta. This research employs a qualitative case study approach, using unstructured interviews and participant observation involving three former prisoners and one mosque community mentor. Data analysis is conducted using General Strain Theory to examine the relationships among post-release pressures, emotional responses, and the tendency to reoffend. Findings indicate that former prisoners experience ongoing economic difficulties and social stigma, which increase vulnerability to recidivism. Mosque communities serve as alternative social spaces that offer religious mentorship, social support, and adaptive coping mechanisms to address these pressures. Religious guidance contributes to emotional regulation and the development of more constructive life orientations. This study concludes that mosque-based communities serve as effective informal social actors in supporting social reintegration and preventing recidivism among former prisoners.